PENGELOLAAN KELAS PADA PEMBELAJARAN AKHLAK DI SEKOLAH DARUL ISLAH RANGAE NARATHIWAT THAILAND - Kholilur Rahman; Ainur Rizqiyah (INCARE, International Journal of Educational Resources, 2022)
This research was conducted at darul islah school located in Rangae, Narathiwat, Southern Thailand. Darul Islah School is one of the schools located in Rangae village city, which implements two leadership systems so as to make class management very varied in each field or subject system. This type of research is using qualitative research methods. The determination of the subject used is purposive sampling with the object of research class management activities consisting of class management of learners and physical management of the class, inhibitory factors and efforts made to overcome inhibitory factors in class management. Research data is collected through semistructured interviews, participatory observations, and documentation. The results showed that in observations, interviews, and documentation there are several things that teachers do to manage the classroom, including, Teachers use freedom and socio-emotional approaches, coaching techniques and the application of discipline provided by teachers in the form of preventive measures, maintenance and improvement of discipline of teacher students to impose curative actions, Teachers create a conducive classroom climate by providing advice, Teachers manage learning interactions with teachers. Applying a conventional learning system, the Teacher applies punishment in the form of tadarus or read surah Yasin, doing tasks, sucking bitter types of plants, while gifts in the form of gifts. In the physical arrangement of the classroom, the teacher gives freedom to students to organize their respective classrooms.